2018
DOI: 10.1142/s1793292018500868
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Defects-Rich 0D/2D α-Fe2O3/g-C3N4 Z-Scheme Photocatalyst for Enhanced Photooxidation and H2 Evolution Efficiencies

Abstract: Rational design and construction of Z-scheme photocatalysts have received much attention in the fields of organic pollutants degradation and H2 evolution because of their potentials to solve the current environmental and energy crises. Herein, a novel nitrogen defects-rich 0D/2D [Formula: see text]-Fe2O3/g-C3N4 Z-scheme photocatalyst was fabricated via a one-pot co-pyrolysis method. Quantum-sized [Formula: see text]-Fe2O3 dots with a diameter of approximately 5[Formula: see text]nm were uniformly distributed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…They are correlated to the vibration of Fe 3+ -O −2 bounds in tetrahedron FeO 4 and octahedron FeO 4 , respectively. [17,30,38] The peaks at 1,637 and 3,436 cm −1 are attributed to water on the surface of the photocatalyst. [20] X-ray photoelectron spectroscopy (XPS) measurements ( Figure 3) were carried out to investigate the chemical states of the surface composition in 2.95% α-Fe 2 O 3 /FL g-C 3 N 4 nanocomposites.…”
Section: Structural and Compositional Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…They are correlated to the vibration of Fe 3+ -O −2 bounds in tetrahedron FeO 4 and octahedron FeO 4 , respectively. [17,30,38] The peaks at 1,637 and 3,436 cm −1 are attributed to water on the surface of the photocatalyst. [20] X-ray photoelectron spectroscopy (XPS) measurements ( Figure 3) were carried out to investigate the chemical states of the surface composition in 2.95% α-Fe 2 O 3 /FL g-C 3 N 4 nanocomposites.…”
Section: Structural and Compositional Characterizationmentioning
confidence: 99%
“…, amino groups (C─NH), and the charging effects in heterocycles, respectively. [17,30] The highresolution spectrum ( Figure 3c) of O 1s shows three peaks at 529.7, 531.9, and 533.1 eV, which are attributed to lattice oxygen, surface hydroxyl groups, and O═C, respectively. The calcination process of g-C 3 N 4 exposed to a large area of air is beneficial to the formation of C═O bonds at the edges.…”
Section: Structural and Compositional Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The X-ray photoelectron spectroscopy (XPS) analysis images of CN, PCN, and Co@PCN are given in Figure 3 , and the atomic percentages of these particles are listed in Table 1 . In the C 1s spectrum ( Figure 3 b) of CN, the peaks at 285.08 and 288.28 eV were attributed to the sp 2 graphitic carbon (C–C=C) and sp 2 -bonded carbon in the triazine rings (N–C=N), respectively [ 43 ]. CN has a lower area ratio of graphitic carbon than PCN, and C–O (289.48 eV) appeared.…”
Section: Resultsmentioning
confidence: 99%
“…A lot of research has revealed that the PEC performance of α‐Fe 2 O 3 is closely related to its morphologies and sizes, meaning that construction of α‐Fe 2 O 3 nanoarrays can greatly enhance the PEC efficiency of α‐Fe 2 O 3 ‐based photoelectrodes 150‐152 . In addition, combining α‐Fe 2 O 3 and g‐C 3 N 4 to form the heterojunctions is also an effective way to improve the PEC performance thanking the increased separation efficiency of photogenerated electrons/holes 66,153 . On the basis of the above reasons, the fabrication of α‐Fe 2 O 3 /g‐C 3 N 4 heteroarray photoanodes could lead to breakthrough progress for water oxidation.…”
Section: Small Bandgap Metal Oxide/g‐c3n4 Heteroarrays As Photoanodesmentioning
confidence: 99%